Molecular genetics of Simulium (Wilhelmia) equinum (Linnaeus) (Diptera: Simuliidae) from West Siberia - Vaulin, Oleg V.; Petrozhitskaya, Liudmila V.; Novgorodova, Tatiana A. (Zootaxa, 2022)
The medico-parasitological importance of bloodsucking black flies is high. To assess potential epidemiological risks and develop biological control programs for these bloodsucking Diptera, it is necessary to be informed of their diversity, community structure and the most common and dominant species. The degree of homogeneity of molecular genetic characteristics of one of the most widespread black fly species Simulium (W.) equinum (Linnaeus) in different parts of its range was investigated. The features of S. equinum from West Siberia where the species has become an abundant ecosystem component in recent years have been revealed. Analysis of species-diagnostic DNA-fragments (COI, ITS2 and D2 28S) in the specimens studied from this region, from the Novosibirsk Oblast (Russia) and data from the DNA database revealed four distinct branches tentatively referred to as West-European, East-European, Finland-Turkish, and Novosibirsk. Specimens from the Novosibirsk Branch were closer to the Finland-Turkish branch. We simulated restriction patterns of the standard COI fragment for all the branches. Substantial level of differences among the branches (4.1–14.8 % by COI sequences) raised the issue of their species status. A further study of S. equinum from West Siberia may clarify the ecological and medico-parasitological features of the Novosibirsk Branch of the species.